Design Strategy toward Recyclable and Highly Efficient Heterogeneous Catalysts for the Hydrogenation of CO2 to Formate - Gunasekar, Gunniya Hariyanandam; Shin, Jeongcheol; Jung, Kwang-Deog; Park, Kiyoung; Yoon, Sungho (AMER CHEMICAL SOC, 2018)
One bottleneck in the realization of CO2 conversion into value-added compounds is the lack of catalysts with both excellent activity and recyclability. Herein, a catalyst is designed for the hydrogenation of CO2 to formate to boost up these features by considering the leaching pathway of previously reported heterogenized catalyst; the design strategy incorporates oxyanionic ligand(s) in the coordination sphere to provide a pathway for both preventing the deleterious interactions and assisting the heterolysis of H-2. The tailored heterogenized catalyst, [bpy-CTF-Ru(acac)(2)]Cl, demonstrated excellent recyclability over consecutive runs with a highest turnover frequency of 22 700 h(-1), and produced a highest formate concentration of 1.8 M in 3 h. This work is significant in elucidating new principles for the development of industrially viable hydrogenation catalysts.
Keywords: EFFECTIVE CORE POTENTIALS; COVALENT ORGANIC FRAMEWORKS; IR-III COMPLEXES; CARBON-DIOXIDE; FORMIC-ACID; MOLECULAR CALCULATIONS; HOMOGENEOUS HYDROGENATION; AMBIENT-TEMPERATURE; IRIDIUM COMPLEX; GRAPHENE OXIDE